Investigating the Efficacy and Safety of Thalidomide for Treating Patients With ß-Thalassemia: A Meta-Analysis - Lu, Yanfei; Wei, Zhenbin; Yang, Gaohui; Lai, Yongrong; Liu, Rongrong (Frontiers in Pharmacology, 2022)
At present, the main therapies for β-thalassemia patients include regular blood transfusion and iron chelation, associating with a number of limitations. Thalidomide, a fetal hemoglobin (HbF) inducer that promotes γ-globin gene expression, has been reported to be effective for β-thalassemia. Thus, this meta-analysis was conducted to assess the efficacy and safety of thalidomide for treating patients with β-thalassemia. We searched the related studies from 8 databases published from inception until October 10, 2021. The R 4.0.5 language programming was used to perform meta-analysis. After screening of retrieved articles, 11 articles were included that enrolled a total of 352 patients. The Newcastle-Ottawa Scale (NOS) was used to evaluate the quality and the bias risk of the included studies. After treatment with thalidomide, the pooled overall response rate (ORR) was 88% (95% confidence interval (CI): 82–93%), and the pooled complete response rate (CRR) was 51% (95% CI: 26–76%). A statistically significant increase in hemoglobin (Hb) level and HbF level after treatment, while there was no statistically significant difference in adult hemoglobin (HbA) level, spleen size, and serum ferritin. According to the results of ORR and CRR, transfusion-dependent thalassemia (TDT) patients showed remarkable efficacy of thalidomide, 85% and 49% respectively. So we analyzed 30 TDT patients from 3 studies and found that the most frequent β-globin gene mutations were 41-42, while response to thalidomide did not show any statistically significant relationship with XmnI polymorphism or 41-42 mutation. About 30% of patients experienced mild adverse effects of thalidomide. Collectively, thalidomide is a relatively safe and effective therapy to reduce the blood transfusion requirements and to increase Hb level in patients with β-thalassemia.